Enhancing the Cytotoxic Effects of Carboplatin and Cisplatin on Liposomes in Oral Cancer Cells with Curcumin - Saeidi, Nastaran; Ansarikojouri, Mandana; Mardani, Maryam; Rezazadeh, Reza; Khanlari Goodarzi, Mahyar; Amiri, Faezeh (Asian Pacific Journal of Cancer Biology, 2024)
Background: Oral squamous cell carcinoma remains challenging to treat effectively with conventional chemotherapy, leading researchers to explore synergistic combinations to enhance therapeutic outcomes. Combining curcumin with platinum-based drugs, such as cisplatin and carboplatin, has demonstrated potential in enhancing cytotoxic effects. However, limited studies have explored these combinations’ efficacy and sustained release profile in liposomal form specifically for oral cancer. This study investigates the enhanced cytotoxic effects of cisplatin-curcumin and carboplatin-curcumin nanoliposome formulations on CAL 27 oral cancer cells. Methods and Materials: Nanoliposomes encapsulating cisplatin or carboplatin with curcumin were formulated and characterized by particle size, zeta potential, and polydispersity index (PDI) to ensure optimized delivery properties. Particle sizes of the cisplatin and carboplatin nanoliposomes ranged from 175 to 187 nm, with a zeta potential greater than -30 mV, indicating good stability, and PDI values less than 0.48, suggesting uniform particle size distribution. In vitro cytotoxicity was assessed using the MTT assay at 24, 48, and 96 hours across different curcumin concentrations. Results: Cisplatin-curcumin and carboplatin-curcumin nanoliposome formulations demonstrated significantly increased cytotoxicity in CAL 27 cells compared to control groups. Drug release studies indicated a sustained release profile, with approximately 22% of cisplatin and 28% of carboplatin released over 52 hours, which may prolong therapeutic effects by maintaining drug availability within the cancer cells. Conclusion: The findings suggest that cisplatin-curcumin and carboplatin-curcumin nanoliposomal formulations enhance the cytotoxic effects of these chemotherapeutic agents while providing a stable, sustained release profile.